Profile Matching Based Business Incubator Tenant Acceptance System - Sugiarto; Pratama Wirya Atmaja (International Journal of Computer, Network Security and Information System, 2020)
Abstract — Business incubator is an institution that is currently more needed to improve all types of entrepreneurs and startups. Tenant is the name of the fostered partners in the Business Incubator, the performance of the Business Incubator is improved, so the tenants who enter the registration in the Business Incubator also increase. The criteria to be a tenant has many variables, so it takes a long time during the calculation process, with the matching profile that can be customized with several variables needed in this business incubator, it becomes a shorter process and provides a recommendation value for the business incubator director in deciding whether the tenant is accepted or rejected. In table 2 in this paper it is explained that the validity test value of the tenant registration information system using the profile matching algorithm gets values above 0.6 of 1, so that the matching profile matching with the case study registration can be applied to the determination of technopark business incubator fostered tenants. Keywords — profile matching, business incubator, validity test;